The implementation of dual vocational education and training in Spain: Analysis of company tutors in the tourism sector - Josefa-Rosa Marrero-Rodríguez; David Stendardi (International Journal for Research in Vocational Education and Training (IJRVET), 2023)
Context: Vocational education and training (VET) has become a key issue in today's highly dynamic business, technological and economic environment, with a complex diversity of systems within the European Union. This paper aims to study the implementation of dual VET in Spain, focusing on the working conditions of company tutors in the tourism sector of Andalusia and the Canary Islands. Approach: Dual VET has been implemented in different ways, both between the different autonomous regions and professional areas since it was launched in 2012. In order to analyse these differences, interviews with teachers, head teachers, students and company tutors were carried out, between 2020 and 2021, in centres that had implemented dual vocational education training and centres that had not. The educational programme in dual VET implies a closer collaboration between schools and companies, as both are active training areas; the training objectives are shared between the school and the company. In this study, the company tutor is studied in his or her facet as trainer and assessor; but special emphasis is placed on the characteristics of the tourism sector, given its relevance in understanding the educational processes involved. Three dimensions underpin the analysis: the characteristics of the company tutor, the training and assessment processes implemented and the link that both maintain with the dynamics of tourism companies. Findings: In general terms, the initial assumptions put forward are confirmed. Firstly, the educational centre leads the process, taking the initiative yet without having the conditions of governance and negotiation typical of the Germanic countries from which these vocational education training systems originate. Secondly, the main characteristics of the company tutor are heterogeneity and informality. Thirdly, the contents and methodology are conditioned by the characteristics of the tourism sector. And finally, assessment also follows informal and changing procedures, generating tensions between the educational centre and company. Conclusions: These results give rise to some theoretical reflections. If the education system is an institution based on the principle of equality, it is worth asking to what extent dual VET can alter this principle, as the company adapts some of the contents and learning outcomes to its specific needs. In addition, an important differentiating factor that marks the learning dynamics has been detected: the size of the company. The difference in size may also influence the future prospects of trainees joining the workforce after completion of VET studies.
urn:nbn:de:gbv:18-10-1050-1
Keywords: 330; Vocational Education and Training; VET; Dual VET; Spain; Company Tutors; Tourism Sector